Harley the hero - Collins, Peggy, 1975- (Pajama Press Inc., 2021)
Harley the service dog is on the job! He goes to school every day with Ms. Prichard to make sure she feels safe. Their students are a lot of fun, but Harley can't play with them while he's wearing his work vest. They write him lots of letters instead, and everything is perfect in the best, most quiet class in the whole school. Until the day the old stage curtains catch fire. As the fire alarm blares, Harley remembers that Ms. Prichard isn't the only human in his class who gets upset by loud noises. Inspired by a true story, Harley the Hero celebrates the work of service animals and the normalization of neurodivergence.